The effects of probabilistic insurance on the capital budgeting decision in respect of a value based management - Michael Zons; Martin Kalveram (Universität zu Köln, Institut für Versicherungswissenschaft, 2005)
As emprical studies show, the policyholders' willingness to pay depends on the security level of the insurance cover. The choice of the security level determines the capital budgeting decision and therefore the cost of capital, as well as the attainable insurance premiums. We call this cost of capital-effect and premium-effect. Hence, the choice of the security level seems to be an important aspect of value based management. In this context, the description of the policyholders' willingness to pay in dependence of the security level is of special interest. In particular Wakker/Thaler/Tversky (1997) develop an explanation of the policyholders willingness to pay for probabilistic insurance based on Prospect Theory. In our paper, we describe and compare the cost of capital-effect and the premium-effect for varying security levels, supported by an example. Under symplifying assumptions, our pragmatic model determines the value proposition of different security levels. Therefore, it generates important knowledge for value based management.
Keywords: 360